2013
DOI: 10.17269/cjph.104.4053
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Neighbourhood Marginalization and Pedestrian and Cyclist Collisions in Toronto Intersections

Abstract: T raffic-related collisions comprise a significant proportion of preventable injury. In 2009 the World Health Organization ranked road traffic accidents the ninth leading cause of death, accounting for 1.21 million deaths and up to 50 million injuries per year. 1,2 Worldwide, nearly half of people who die in traffic collisions are vulnerable road users: pedestrians, cyclists and motorized 2-wheeler users. 2 In Canada, there were 199,337 road-traffic-related injuries and 2,889 fatalities in 2006; pedestrians co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…With about a million people in the suburbs and a total population of 3,372,660, Mashhad has the largest suburban population in Iran [13], which translates into a large population of poor children [13]. Moreover, being a child, or a member of a low-income family, are two known risk factors for pedestrian accidents [14][15][16]. Paediatric, Pedestrian Road Traffic Injuries (PPRTIs) is, therefore, an important and crucial public health issue for this city, whose reduction would require effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…With about a million people in the suburbs and a total population of 3,372,660, Mashhad has the largest suburban population in Iran [13], which translates into a large population of poor children [13]. Moreover, being a child, or a member of a low-income family, are two known risk factors for pedestrian accidents [14][15][16]. Paediatric, Pedestrian Road Traffic Injuries (PPRTIs) is, therefore, an important and crucial public health issue for this city, whose reduction would require effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted by Silverman (2013) also supports this claim. However, they examine the number of cyclist collisions in Toronto connecting them to socio-demographic factors in the Ontario Marginalization Index rather then health and disease (Silverman, 2013).…”
Section: Table 22: Ontario Marginalization Index Indicators On-marg D...mentioning
confidence: 54%
“…This study is particularly interesting as it takes place in Toronto as well. On-Marg data was applied to each intersection where the collisions occurred, and a logistic regression analysis was performed to examine the association between the four ON-Marg dimensions and the cyclist collisions (Silverman, 2013). Based on these dimensions, they concluded that local areal dependency and material deprivation were not significant factors in the cyclist collision (Silverman, 2013).…”
Section: Table 22: Ontario Marginalization Index Indicators On-marg D...mentioning
confidence: 99%
“…These results should provide guidance to the numerous studies aggregating health outcomes to the census tracts in which they occur, especially those investigating outcomes that may be geographically associated with census boundaries. Pedestrian injury in general, and child pedestrian injury in particular, is one area where the growing body of research [ 13 16 , 21 , 25 , 26 28 ] is becoming aware of inherently geographic issues within their studies–those identified through this investigation should be added to the list.…”
Section: Discussionmentioning
confidence: 99%